Réponses

2013-05-22T16:25:02+02:00

Rassemble ce qui va ensemble.

 

3 + 4(2x - 1) = 3(x + 5) - 2

3 + 8x - 4 = 3x + 15 - 2

8x - 1 = 3x + 13

8x - 1 + 1 = 3x + 13 + 1

8x - 3x = 3x + 14 - 3x

5x / 5 = 14/5

x = 14/5 = 2,8

 

-3 - 7(2x + 2) = 4(-1 - x)

-3 - 14x - 14 = -4 - 4x

-14x - 17 = -4 - 4x

-14x - 17 + 17 = -4 - 4x + 17

-14x + 4x = -4x + 13 - 4x

-10x / 10 = 13/ -10

x = -1,3

  • Utilisateur Brainly
2013-05-22T16:42:06+02:00

a)

3+4(2x-1)=3(x+5)-2

3+4*2x+4*(-1)=3*x+3*5-2

3+8x-4=3x+15-2

-1+8x=3x+13

-1+8x+1=3x+13+1

8x=3x+14

8x-3x=3x+14-3x

5x=14

x=14/5

x=2.8

 

b)

-3-7(2x+2)=4(-1-x)

-3-7*2x-7*2=4*(-1)+4*(-x)

-3-14x-14=-4-4x

-17-14x=-4-4x

-17-14+4x=-4-4x+4x

-17-10x=-4

-17-10x+17=-4+17

-10x=13

x=13/-10

x=-1.3

 

voilà...... :)